Relationship between void characteristics and re-liquefaction resistance: An image analysis study - R. Sukhumkitcharoen; J. Koseki; M. Otsubo (Soils and Foundations)
To scrutinize the impact of void characteristics on re-liquefaction resistance, a series of constant-volume cyclic bi-axial tests was conducted on an assembly of plastic rods. The first and second liquefaction stages involved the application of isotropic compression at 100 kPa followed by constant-volume cyclic loading with the deviator stress set at 30 or 60 kPa. This study introduced an innovative image analysis method to quantify four void characteristics: anisotropy index (Ie) and average void element size (Ae) for the element-based analysis, and local anisotropy index (Ie,ij) and local void ratio (eij) for the grid-based analysis. The newly developed anisotropy index was seen to facilitate the assessment of the primary alignment and degree of anisotropy in void elements. The results confirmed that an increase in re-liquefaction resistance is evident in specimens with lower average eij, coefficient of variation (CV) of eij, and Ie, indicating denser, more homogeneous, and isotropic conditions. Nevertheless, specimens with a greater degree of anisotropy were found to be more susceptible to re-liquefaction. The development of strain in the early stages of cyclic loading was found to be predominantly influenced by the anisotropy index, underscoring the imperative need for an enhanced method that can predict liquefaction resistance, as well as re-liquefaction resistance, and incorporates the anisotropy index.